Produtividade e retorno econômico sob doses de nitrogênio em lavouras de milho irrigado e sequeiro, no município de Buri - SP - Oliveira, Gustavo Raphael de (Universidade Federal de São Carlos, 2022)
Nitrogen is essential in corn and the rising prices of this fertilizer become a big problem for producers. Therefore, this research was carried out with the central objective of analyzing the influence of different doses of nitrogen on productivity and economic return in irrigated and rainfed maize under crop conditions, in the municipality of Buri - SP. The treatments in each environment consisted of 4 doses of nitrogen in topdress in the form of urea (40, 80, 120 and 160 kg ha-1) and the experimental design was randomized blocks, with 8 replications. The yield of corn grains in the rainfed and irrigated environments and the economic viability of the nitrogen doses used in the experiments were evaluated. The results showed that there was no significant difference between the averages of nitrogen doses within each environment, however, when analyzing the averages of corn grain yield between the rainfed and irrigated environments, higher productivity was observed in the irrigated environment. Regarding the economic analysis, the highest economic return was verified at the dose of 80 kg ha-1 of N in topdress, being more expressive in the rainfed crop. This research suggests that studies on reducing the dose of N can signal optimization of the use of urea, allowing greater profitability for producers and ensuring a more sustainable agriculture.
Productivity and economic return under doses of nitrogen in irrigated and rainfed maize crops, in the municipality of Buri - SP
Keywords: Zea mays; Fertilizante; Sustentabilidade; Fertilizer; Sustainability; CIENCIAS AGRARIAS